Experimental investigation on hygrothermal behaviour of cement and lime plaster. (1st June 2022) - Damle, R.M.; Khatri, N.; Rawal, R.
Abstract: Traditional buildings since many centuries have used lime as a binder and finishing material. However, in contemporary construction practices, lime mortar and lime plaster have been replaced by cement mortar and cement plaster. Lime is a sustainable and self-healing material whose strength increases with time. In addition to its pleasing appearance, lime has excellent moisture buffering properties. Buildings with lime mortar and lime plaster are also breathable due to moisture transfer across the envelope. The objective of this work is to compare the hygrothermal performance of lime and cement plaster. For this purpose, two identical test cells of 1 m 3 volume were constructed with brick as masonry material. One of the test cells was built with cement mortar and cement plaster, while the other cell was made with lime mortar and lime plaster. Environmental variables such as indoor air temperature, indoor relative humidity, globe temperature, surface temperatures, surface moisture content were monitored for a period of 74 days. It was found that the lime test cell was cooler by 3–5 °C and the indoor conditions were comfortable for 40% more time. The moisture buffering capacity of lime also helped to moderate the indoor relative humidity. The above differences were observed when the test cells passively responded to the changing outdoor conditions without internal loads. Further investigation of real-sized spaces would be necessary to endorse the advantages of lime plaster found in this study. Highlights: Lime and cement plastered test cells monitored for a period of 74 days. Lime plaster reduces indoor temperature by 3–5 °C and moderates relative humidity. Comfort hours in lime test cell higher by 40%. Hygrothermal properties of lime and cement plaster have been reported.